Locating the channel and other tales from the river bank: constants and change in river boundary delimitation. Issue 6 (18th August 2022) - Schofield, Richard
ABSTRACT: Nowhere is the contrast between the top-down process of drawing a boundary and the ground-up reality of living with it so obvious as in delimitations along rivers – live features not just physically but also, potentially, navigable arteries. Illustrations are drawn from the chequered history of two famous colonial river boundaries along the Shatt al-Arab and Jordan rivers; and in the invocation of history in legal settlements of the status of Kasikili/Sedudu Island in the Caprivi Strip (1995–99) and the Abyei region on the Bahr al Arab between Sudan and South Sudan (2008–09).